Survival outcomes of intrathoracic vs. cervical anastomosis post-esophagectomy in middle and lower thoracic esophageal squamous cell carcinoma: a retrospective propensity score matching analysis - Wei, Xueqiang; Mao, Jie; Bai, Yuncheng; Yang, Hao; Peng, Yizhou; Liu, Jin; Shen, Zhenghai; Gao, Shengguai; Wang, Huiqiao; Chen, Xiaobo; Chen, Ying; Yang, Jiapeng; et al. (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to compare long-term survival outcomes between cervical anastomosis (CA) and intrathoracic anastomosis (IA) in patients with middle and lower thoracic esophageal squamous cell carcinoma (ESCC).MethodsA retrospective cohort analysis was conducted on 571 patients who underwent esophagectomy at a single institution. Patients were stratified into CA and IA groups based on anastomotic technique. Propensity score matching (PSM, 1:1) was applied to balance baseline covariates. Overall survival (OS) and disease-free survival (DFS) were evaluated using Kaplan-Meier analysis and Cox regression. Secondary outcomes included postoperative complications.ResultsIn the unmatched cohort, CA demonstrated superior OS (median: 51.17 vs. 34.50 months; HR: 1.368, 95% CI: 1.062–1.763; p=0.015) and DFS (median: 45.07 vs. 28.87 months; HR: 1.289, 95% CI: 1.013–1.641; p=0.039) compared to IA. However, after PSM, the survival advantage attenuated (OS: HR = 1.303, 95% CI: 0.953–1.780, p=0.097; DFS: HR = 1.295, 95% CI: 0.962–1.744, p=0.089). Multivariate analysis identified pathological T3/T4 stages (OS: p=0.002–0.009; DFS: p<0.001) and lymphovascular invasion (DFS: p=0.023) as dominant prognostic factors, overshadowing anastomotic technique. The CA group exhibited more extensive lymph node dissection (>7 stations, p<0.001), but short-term mortality (30-/90-day) did not differ between groups (p≥0.382).ConclusionIn conclusion, our study suggests that there may be a potential survival advantage of CA over IA in patients undergoing esophagectomy for ESCC. However, the initial survival benefits associated with CA diminished after adjusting for confounding factors.